A Beta-return Efficient Portfolio Optimisation Following the CAPM An Analysis of International Markets and Sectors - Vollmer, Markus. (BestMasters,, 2015)
Investors are trying to generate excess returns through active investment strategies. Since the outbreak of the financial crisis, investors face a situation where increased risks are accompanied by falling key interest rates. An optimal portfolio in terms of risk and return becomes a perpetual motion machine. Markus Vollmer answers the question how the seemingly impossible could still be achieved by an empirical analysis of historical data of 1’800 stocks listed at equity markets in 24 countries covering all 19 supersectors. The author offers valid and reliable findings by using the previously mentioned data proxy. He reveals purposefully the need for further research and simultaneously he derives specific and applicable guidelines for the design of investment strategies which are extremely exciting for both the institutional expert and the private investor. Contents Analysis and Evaluation of the Major Capital Market Theories Stock Market Analysis Modelling of an Efficient Portfolio Allocation Targets Teachers and students of economics with an interest in application-oriented stock market research Practitioners in portfolio and asset management departments, investment strategists of institutional investors as well as research analysts at (investment) banks The Author In addition to his lectureship for investment, corporate finance and risk management at the University of Applied Sciences in Stuttgart (HFT Stuttgart), Markus Vollmer presides over the controlling department at a medium-sized company.